2006
DOI: 10.1007/s10803-005-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

The Cambridge Mindreading (CAM) Face-Voice Battery: Testing Complex Emotion Recognition in Adults with and without Asperger Syndrome

Abstract: Adults with Asperger Syndrome (AS) can recognise simple emotions and pass basic theory of mind tasks, but have difficulties recognising more complex emotions and mental states. This study describes a new battery of tasks, testing recognition of 20 complex emotions and mental states from faces and voices. The battery was given to males and females with AS and matched controls. Results showed the AS group performed worse than controls overall, on emotion recognition from faces and voices and on 12/20 specific em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
200
2
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 266 publications
(221 citation statements)
references
References 41 publications
10
200
2
9
Order By: Relevance
“…Harms et al, 2010). However some studies have demonstrated that females with AS perform worse on FER than matched controls such as Golan and colleagues, although these results are based on comparisons between 6 females with ASD and 5 age and IQ matched controls (Golan et al, 2006). However, in support of an affective deficit in females with ASD, a recent study of 33 males and 29 females found that males and females do not differ on selfreported empathy measured employing the Empathy Quotient [EQ] as a broader measure of basic emotional ability (Lai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harms et al, 2010). However some studies have demonstrated that females with AS perform worse on FER than matched controls such as Golan and colleagues, although these results are based on comparisons between 6 females with ASD and 5 age and IQ matched controls (Golan et al, 2006). However, in support of an affective deficit in females with ASD, a recent study of 33 males and 29 females found that males and females do not differ on selfreported empathy measured employing the Empathy Quotient [EQ] as a broader measure of basic emotional ability (Lai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence suggests that measuring FER would be most appropriate for assessing amygdala functioning. However some studies have demonstrated that females with AS perform worse on FER than matched controls such as Golan and colleagues, although these findings are based on 6 ASD and 5 control participants (Golan, Baron-Cohen, & Hill, 2006). Other studies have even smaller gender groups (Golan et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The battery provides an overall facial and an overall vocal emotion recognition score, as well as an overall number of the emotions correctly recognized. Individuals with AS/HFA score significantly lower than controls on all three measures in the battery (Golan et al, 2006b). Test Áretest correlations, calculated for individuals with AS/HFA were r0/.94 for the face task and r0/.81 for the voice task.…”
Section: Autism Spectrum Quotient (Aq; Baron-cohen Et Al 2001b)mentioning
confidence: 90%
“…The Cambridge Mindreading Face ÁVoice Battery (CAM; Golan et al, 2006b) This battery tests recognition of twenty complex emotions and mental states from short silent video clips of faces and from voice recordings. The face task comprises silent clips of adult actors, expressing the emotions in the face.…”
Section: Autism Spectrum Quotient (Aq; Baron-cohen Et Al 2001b)mentioning
confidence: 99%
See 1 more Smart Citation